Recent Trends in Auditing by Uncovering the Digital Age and Best Practices for Efficiency and Accuracy - Ghaniya Arya Gemilang; Ellyona Tehilla Ganish; Niken Dwi Anggraeni; Trinandari Prasetyo Nugrahanti (Journal Markcount Finance, 2024)
This article discusses recent developments in the field of auditing amid the rapidly evolving digital era. In the face of digital transformation, best practices in auditing to achieve higher efficiency and accuracy are the main focus. The discussion includes the application of the latest technology, audit strategies that are adaptive to digital changes, and steps to ensure accuracy in the audit process. Considering the challenges and opportunities that arise in the digital age, this article offers insight for audit professionals looking to strengthen their practices in the face of a dynamically changing business environment.